2008
DOI: 10.1007/s10482-008-9271-x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Multiple-Locus VNTR Fingerprinting in detection of clonality of community- and hospital-acquired Staphylococcus aureus isolates

Abstract: Staphylococcus aureus has become a major source of hospital infections and the risk of colonisation and infection by community-acquired methicillin-resistant S. aureus (CA-MRSA) is increasingly higher. Because of the importance of S. aureus to public health, many molecular typing methods have been developed to determine its transmission routes and source of infection during epidemiological investigations. In this study we evaluated the usefulness of multiplex PCR based Multi-Locus VNTR Fingerprinting (MLVF) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
1
14
0
1
Order By: Relevance
“…In this set of AA-MRSA isolates, the MLVA was not able to distinguish among isolates with the same PFGE profile. In agreement with our results, previously published reports of MLVA typing of clinical MRSA isolates had more discriminatory power than those of spa typing and MLST (12,15,16,17). In contrast, most studies comparing the MLVA with PFGE have shown that the discriminatory power of PFGE was comparable to that of the MLVA or only slightly better.…”
Section: Vol 47 2009supporting
confidence: 92%
See 2 more Smart Citations
“…In this set of AA-MRSA isolates, the MLVA was not able to distinguish among isolates with the same PFGE profile. In agreement with our results, previously published reports of MLVA typing of clinical MRSA isolates had more discriminatory power than those of spa typing and MLST (12,15,16,17). In contrast, most studies comparing the MLVA with PFGE have shown that the discriminatory power of PFGE was comparable to that of the MLVA or only slightly better.…”
Section: Vol 47 2009supporting
confidence: 92%
“…In addition, three recently developed MLVA techniques, successfully applied to Staphylococcus aureus and more specifically to HA-MRSA and CA-MRSA, were evaluated and optimized for use with ST398 strains. Both the initial Polish system (15,16,17,23,24) and the Swiss system (10) are based on tandem repeats in genes, whereas the British system is based on staphylococcal interspersed repeat units, called SIRUs (11,12). In this study, only primers with discriminatory power were included in this optimized MLVA specific for AA-MRSA.…”
Section: Vol 47 2009mentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of our strain collection is biased, based on isolates which differs by PFGE. This has previously been reported to affect the discriminatory ability of MLVF (Holmes et al, 2010;Luczak-Kadlubowska et al, 2008). Furthermore, a better resolution might have been obtained if we had targeted more than five tandem repeat loci.…”
Section: Discussionmentioning
confidence: 87%
“…In the spa sequence typing method, each identified repeat is associated to a code and a spa-type is deduced from the order of specific repeats. Although spa-typing has a lower discriminatory ability than PFGE [45,46], its cost-effectiveness, ease of use, speed, excellent reproducibility, appropriate in vivo and in vitro stability, standardised international nomenclature, high-throughput by using the StaphType software, and full portability of data via the Ridom database (http:// spaserver.ridom.de) makes this method the currently most useful instrument for characterising S. aureus isolates at the local, national and international levels [47][48][49][50][51][52]. Importantly, this approach ensures strict criteria for internal and external quality assurance of data submitted to the database that is curated by SeqNet.org [50,53].…”
Section: Staphylococcus Aureus Protein a Gene-typingmentioning
confidence: 98%